Eliminating human rabies deaths: targeting the elimination of rabies - Cleaveland, OBE, FRS, Sarah (Henry Stewart Talks, 2020)
Prevention and control of rabies in Latin America, Reservoirs of infection in the Serengeti, Transmissibility (R0) of rabies, Effective vs. ineffective methods for rabies control, “Zero by 30” initiative